Sustainability in start-ups: A literature review - Charlotte Mühle; Claudia Nelly Berrones-Flemmig; Cansu Hattula (IU Internationale Hochschule, 2024)
This paper aims to provide a literature review in the area of Sustainability for start-ups. Even though corporate social responsibility has gained importance throughout recent years, it still needs to be implemented properly in the business world. In addition to that, the focus for sustainability practices still lies heavily on larger organizations. Considering that sustainability is relevant for organizations regardless their size or industry, it is important to investigate it in different contexts. Given that operating sustainable is often connected to higher costs, business models which focus on sustainability are usually designed for bigger companies, which makes it complex or even impossible for start-ups to implement them (Halberstadt & Johnson, 2014, p. 1-2). Throughout the past years, the concern about creating value for not only a business itself but also the people affected by it, society in general and the environment itself, has grown and it clearly shows that the traditional way of corporate reporting is not satisfactory anymore since the needs of several stakeholders are not included (Felber, Campos & Sanchis, 2019, p.1). The balance of the common good aims to visualize not only economic success in forms of the balance sheet total or financial results of a business but also the contributions of an organization to the public good (Butscher, Kasper, Koloo & Riedel, 2021, p. 5). Themain research question of this paper is: What value has the implementation of sustainability management for a start-up regarding their competitive advantage? The results of the literature review show that sustainability management and sustainability-promoting concepts are not only common but should be implemented by any company which plans to operate successfully long-term. The balance of the common good is a helpful tool to improve a firm's operations and convert to a more sustainable business model. Therefore, this literature review can be also helpful for start-ups, which are able to implement sustainability management practices in their businesses.
Keywords: M; Q; 650; Sustainability; Balance of the common good; Common good economy; start-ups; Germany